2019
DOI: 10.3390/jcm8030324
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Women after Giving Birth: Associated Factors Related with the Birth Process

Abstract: The World Health Organization (WHO) considers quality of life a fundamental indicator. The effect of birth on women’s long-term quality of life (QoL) has barely been studied. The purpose of this study was to determine the factors related with the pregnancy, delivery and puerperium, and assess women’s QoL after giving birth. A cross-sectional study with Spanish puerperal women was carried out; it collected data on socio-demographic variables, obstetric variables, newborn data, and several quality of life parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
4
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 29 publications
5
39
4
5
Order By: Relevance
“…Therefore, women may perceive their physical health as worse than that of women who had a vaginal delivery [36,37]. Martínez-Galiano et al found that cesarean delivery was associated with a worse overall HRQoL score at six weeks after childbirth in a large sample of Spanish women [8]. The potential effects of a cesarean delivery on HRQoL after childbirth may be taken into consideration when deciding about cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, women may perceive their physical health as worse than that of women who had a vaginal delivery [36,37]. Martínez-Galiano et al found that cesarean delivery was associated with a worse overall HRQoL score at six weeks after childbirth in a large sample of Spanish women [8]. The potential effects of a cesarean delivery on HRQoL after childbirth may be taken into consideration when deciding about cesarean delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Giving birth by a woman and adaptations during weeks after childbirth may have a significant impact on women’s HRQoL. Issues mentioned in the literature such as urinary incontinence and other common health problems may affect HRQoL [5,6,7,8,9,10,11,12,13]. In addition, women’s HRQoL after childbirth may be affected by factors related to pregnancy and delivery [12,14,15], by infant’s health [16], and by non-medical factors, such as race, maternal age, and socioeconomic status [10,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers with a high level of education were one of the factors in the high QoL scores of mothers in labor (Martínez-Galiano, et al, 2019;Rezaei et al, 2016;Zubaran & Foresti, 2011). It happened because a person with higher education was able to control their emotions and social life (Islami, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of correlation between breastfeeding practices and quality of life for mothers was obtained from nine literatures that were reviewed by researchers. Six literatures stated that breastfeeding practices are significantly related to the maternal quality of life (Aminova, et al, 2018;Chen et al, 2007;Grylka-Baeschlin et al, 2014;Kamalifard et al, 2018;Mortazavi, Mousavi, & Chaman, 2014;Zubaran & Foresti, 2011), while three other literatures stated that breastfeeding practices have no significant correlation to the maternal; quality of life (Rezaei et al, 2016;Triviño-Juárez et al, 2016;Martínez-Galiano et al, 2019).…”
Section: Breastfeeding or Not Breastfeeding With M-qolmentioning
confidence: 99%
“…3 Some familiar factors that may affect postpartum QoL ranges widely from mode of delivery, degree of perineal laceration, admission of the mother to the ICU, time since last giving birth, mother's age, gestational diabetes, gestational hypertension, to socioeconomic and educational status. 4 In two studies conducted in Iran, mode of delivery seems to have an impact in women's postpartum QoL. These two studies suggest that vaginal delivery slightly increases QoL compared with Caesarian section.…”
mentioning
confidence: 99%